Tolerance and dependence evoked by an endogenous opiate peptide. - Lampert, A (1976)
Incubation of neuroblastoma X glioma hybrid cells for 12-97 hr with methionine-enkephalin results in an increase in adenylate cyclase activity [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1] that is mediated by the opiate receptor. The results show that cells become tolerant to, and dependent upon, enkephalin.